Merayakan Cinta Berdasarkan Kidung Agung 1:9-17 - Mick Mordekhai Sopacoly (DUNAMIS: Jurnal Teologi dan Pendidikan Kristiani, 2020)
Abstract. At a glance reading the Song of Songs gives the impression as a book that displays mere sensuality. Therefore raising the question why the Song of Songs was included in the canonization of the Bible which is the Word of God. This paper aimed to explore the meaning of the great love found in the Song of Songs text that seems vulgar and sensual. The method used in this study was a historical criticism of the Song of Songs 1: 9-17. Through this study, it could be concluded that the love texts in Song of Songs display the power of love that is unique, creative, and contains a sacred dimension, which not only focuses on the physic, but also in the emotional aspects, conscience, and inner bonds, as a form of celebration of God's grace.Abstrak. Membaca kitab Kidung Agung sekilas memberikan kesan sebagai kitab yang menampilkan sensualitas semata. Hal itu tentunya menggugah pertanyaan mengapa Kidung Agung masuk dalam kanonisasi Alkitab yang adalah merupakan Firman Tuhan. Tulisan ini bertujuan untuk menggali makna cinta yang agung di balik tulisan dalam kitab Kidung Agung yang terkesan vulgar dan sensual. Metode yang digunakan dalam kajian ini adalah metode kritik historis terhadap teks Kidung Agung 1:9-17. Melalui kajian tersebut dapat disimpulkan bahwa teks-teks cinta dalam Kidung Agung menampilkan kekuatan cinta yang unik, kreatif, dan mengandung dimensi kesakralan, yang tidak hanya berfokus kepada fisik, tetapi juga dalam aspek emosional, nurani, dan ikatan batin, sebagai bentuk perayaan atas anugerah Allah.